Influenza vaccination rates, knowledge, attitudes and behaviours of healthcare workers in Turkey: A multicentre study - Korkmaz, Nesibe (Int J Clin Pract, 2020)
AIM: Influenza vaccination is the most effective method in prevention of influenza disease and its complications. Our study aimed to investigate the rates of vaccination and the behaviours and attitudes against the vaccine in healthcare workers in Turkey. METHODS: This multicentre national survey is a descriptive study in which 12 475 healthcare workers. Healthcare workers were asked to answer the questionnaire consisting of 12 questions via the survey. RESULTS: It was found that 6.7% of the healthcare workers regularly got vaccinated each year and that 55% had never had the influenza vaccine before. The biggest obstacle against getting vaccinated was determined as not believing in the necessity of the vaccine (53.1%). CONCLUSION: The rates of influenza vaccination in healthcare workers in Turkey are quite low. False knowledge and attitudes on the vaccine and disease are seen as the most important reasons to decline vaccination. It is important to detect reasons for anti‐vaccination and set a course in order to increase the rates of vaccination.